O renascimento psíquico vivido em análise - Araujo, Ana Karina Fachini (2018)
The present dissertation has as object of study the process of psychic rebirth lived under analysis. It is intended to present and discuss the analysis, as a possibility of psychic rebirth. More specifically, the proposition was to analyse the process that involves this phenomenon, in the dialectical movement to idealize and "de-idealize", considering the experience through the Oedipal situation and depressive position, with the report and discussion of two clinical cases. This dissertation was guided by the psychoanalytical method. The psychoanalytic theoretical framework underpinned this study and its analysis, with Melanie Klein, Winnicott and Balint as main authors. In both cases under analysis, it was possible to follow the experience of psychic rebirth. In this program, patients were able to retrieve their experience with the good object and then proceeded and progressed towards the elaboration of the depressive position and Oedipal situation. In the journey of analysis, the patient's need was considered, in the sense of regressing to both dual and idealized relationships with the analyst object; lasting in that more dependent performance, for the time necessary, to meet his/her needs; and thereby ensure a secure and safe environment in which the good object could be retrieved and then trust it. Thus, the relations with the analyst object and, consequently, with the other objects, went from ideal to more integrated and, therefore, the patients at issue could acquire more resources before the task of living and existing